Acceleration of Paraquat Biodegradation by Isolated Soil Bacteria - Erni Martani; Nur Arfa Yanti; Sebastian Margino; Sri Noegrohati (Universitas Gadjah Mada, 2002)
Herbicides residues were reported to have impact on the ecosystem. It was thought that acceleration of paraquat degradation would minimize these impacts. Paraquat was persistent in peat soil due to low pH. This study was done to investigate the role of bacterial isolates on the acceleration of paraquat degradation, especially in peat soil. The bacteria were isolated from several kinds of Indonesian soils using enrichment culture technique in a modified N-free medium. The medium was added with paraquat at gradually increase-concentration from 10, 20, and 40 ppm (w/w). Examinations in paraquat degradation were done in two levels. The first was in a synthetic medium (N-free medium); the second was in soil extract medium. Two kinds of peat were used to make the soil extract media, i.e. fibric and saphric peat soils. Several bacterial isolates were able to degrade paraquat in N-free medium. However, the degradation mode was different with those in peat soil extract media. None of them degraded paraquat in fibric and saphric soil extract media. It was suggested that the environmental limiting factors were responsible to the failure of paraquat degradation. Two selected isolates were able to degrade paraquat when the pH value of the extract medium was enhanced to around 5.5. Bacterial isolate of SM1, which was isolated from acid sulfate soil of Central Kalimantan, was the best isolate which was able to degrade paraquat in synthetic medium and peat soil extract media, especially in fibric extract medium. It degraded around 30%of paraquat within 15 day. Experiments are being done to enhance paraquat degradation by inoculation of mixed cultures of selected bacterial isolates.